Morphological Assessment Of Epithelium and Nucleus in Oral Submucous Fibrosis Individuals - Rida Rubab Ahmed, Ambeen Usmani, Muhammad Shahid, Mazhar Ul Haque, Imran Khan Khattak, Ashfaq Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate histomorphological alterations present within nucleus and epithelium in oral submucous fibrosis subjects Methods: This study recruited 50 clinically diagnosed cases of oral submucous fibrosis which were active chewers of areca nut and associated products. Oral mucosa tissue blocks were prepared and processed followed by staining with Hematoxylin & Eosin to observe morphological features. The findings were statistically analyzed through SPSS version 23 Results: Amongst the sample size of 50, 33(66%) of cases had pleomorphic nuclear structure out of which 21(91.3%) had prominent nucleoli. High statistical significance was appreciated relating to involvement of nuclear and nucleoli structure. In addition, epithelial demarcation was appreciated within epithelium present in disease. 37(74%) cases were histologically identified cases of fibrosed structure out of which 31(83.8%) of the subjects had hyperplasia in epithelial lining. Hyperplastic epithelium was significantly correlated with OSMF. However, strength of association was weak with a p value of 0.04 Conclusion: The results revealed pleomorphism in nuclei underlining a strong association of structural alteration with disease initiation and progression. Hyperplastic stratified squamous epithelium was found in abundance which could be attributed to adaptive response of epithelium to inflammatory alkaloids present in areca nut products. Such findings could serve as trigger factor for oral submucous fibrosis and should be considered significant for early diagnosis and treatment management.